A Survey on Webmining and Web Usuageminig - Ramajayam, G; Soundharya, V; Likitha, M.S (International Journal of Computer Sciences and Engineering, 2025)
The World Wide Web has extremely huge amount of information and it facilitates the user to search for data by moving from one document to another. Web mining is the application of Data mining and it is the procedure of discovering and extracting fruitful information from extremely large web data. The web is rapidly began to modernize and enlarged. In such case web mining is becoming a challenging task. It has to handle different communities, different external interfaces etc. In this paper we are focusing on web mining process and one of its type, web usage mining. This paper covers the basic concept of web mining and detailed description of web usage mining